Analysis of the competitive performance of the SAIDAL Complex under strategic alliances - Mahboub, Fatima; Snoussi, Oussama (Milev Journal of Research and Studies, 2017)
SAIDAL complex in Algeria is one of the industrial enterprises that have adapted to the economic changes and developments in the global external environment by adopting the alliance with the world's largest laboratories, which varied between the mixed partnership and the integrated alliances. In order to know the effect of this strategy on its competitive performance We have relied on a questionnaire by distributing a questionnaire with the objective of knowing the views of managers and staffs on the impact of these alliances on the competitive performance of this industrial complex.